342 SURGICAL TREATMENT OF ESOPHAGEAL CANCER WITH VARIATIONS OF THE AORTIC ARCH AND ITS BRANCHES. (17th September 2021) - Li, Baiwei; Dai, Liang; Jiang, Haoyao; Li, Zhigang; Chen, Keneng
Abstract: : The variations of the aortic arch and its branches are rare. The surgical treatment of esophageal cancer would be challenged for combination with this anomaly. This study intends to review significant group cases to analyze the influence of this variation on esophagectomy. Methods: From 2013 to 2019, 19 patients with aortic arch and brachiocephalic vessels variations underwent esophagectomy, accounting for 0.3% during the same period. The abnormalities were distributed as follows: left-sided aortic arch combined with aberrant right subclavian artery (LAA + ARSA) occurred 13 cases, right-sided aortic arch anomalies with mirror image arch branches (RAA + MIAB) in 1 case, and right-sided aortic arch combined with aberrant left subclavian artery (RAA + ALSA) in 5 case. Of the patients with LAA + ARSA, 11 patients underwent the McKeown esophagectomy, and 2 patients via transhiatal. All patients with RAA underwent left thoracotomy approach.Perioperative outcomes and long-term survival were analyzed. Results: The tumors were mostly located in the upper and middle thorax (47.4% and 42.1%). The R0 resection rate was 89.5% (17/19). Recurrent laryngeal nerve injury occurred in 2 patients, anastomotic fistula in 1 patient. Two patients died within 30 days postoperatively. The yield of lymph nodes was 21.8 ± 9.4. The sampling rate of lymph nodes along the recurrent laryngeal nerve was 61.5% in LAA + ARSA group, while 16.7% in RAA group. Recurrence happened in 5 cases (29.4%), including 2 regional relapse. Four patients died after recurrence, with a median time to death of 20 months (range: 10–48 months). Conclusion: For aortic arch and brachiocephalic artery variations in esophageal cancer, aberrant right subclavian artery and right-sided aortic arch are the most common types. The surgical strategy is closely related to the aortic arch position. Due to the combined variation of the recurrent laryngeal nerve, the upper mediastinal lymph nodes dissection would be conservative, but with acceptable oncologic results.